A facile synthesis of highly luminescent nitrogen-doped graphene quantum dots for the detection of 2, 4, 6-trinitrophenol in aqueous solution. Issue 5 (19th December 2014) - Lin, Liping; Rong, Mingcong; Lu, Sisi; Song, Xinhong; Zhong, Yunxin; Yan, Jiawei; Wang, Yiru; Chen, Xi
Abstract : Fluorescent N-GQDs with a high quantum yield of 59.2% have been synthesized by pyrolyzing CA and Tris-HMA. The N-GQDs emitted strong blue fluorescence under 365 nm UV light and their fluorescence intensity showed a sensitive response to TNP in the range 1–60 μM. Abstract : A facile bottom-up method for the synthesis of highly fluorescent nitrogen-doped graphene quantum dots (N-GQDs) has been developed via a one-step pyrolysis of citric acid and tris(hydroxymethyl)aminomethane. The obtained N-GQDs emitted strong blue fluorescence under 365 nm UV light excitation with a high quantum yield of 59.2%. They displayed excitation-independent behavior, high resistance to photobleaching and high ionic strength. In addition to the good linear relationship between the fluorescence intensity of the N-GQDs and pH in the range 2–7, the fluorescence intensity of the N-GQDs could be greatly quenched by the addition of a small amount of 2, 4, 6-trinitrophenol (TNP). A sensitive approach has been developed for the detection of TNP with a detection limit of 0.30 μM, and a linearity ranging from 1 to 60 μM TNP could be obtained. The approach was highly selective and suitable for TNP analysis in natural water samples.